MANAGING RESISTANCE IN SCHOOL/MADRASAH MANAGEMENT TOWARDS THE GLOBAL ERA - Erland Cahyo Saputro; Imam Makruf (RADJA PUBLIKA, 2025)
This study aims to identify attitudes and factors influencing resistance to change within educational organizations, as well as to formulate effective strategies for managing such resistance so that changes can be accepted and successfully implemented by all stakeholders in schools or madrasahs. This research employs a library research approach. The results indicate that school or madrasah management must be sensitive and continuously improve their ability to understand and control resistance to change. Furthermore, school or madrasah principals play a strategic role in guiding the organization toward positive transformation.